Jesus as teacher, master. The appellative names of the Son of God in the Old Polish and 16th century translations of the Gospel - Kępińska, Alina (Philology as the Ordering of Chaos: Language and Text Studies. Ad honorem Professoris Marci Cybulski, 2018)
The subject of the article are different appellative names of Jesus occurring in the Old Polish and 16th century translations of the Gospel, categorized into the names used by himself and his disciples. Those names include: mistrz, uczyciel, nauczyciel, przykażyciel, przystaw, rabbi or rabbuni. These are different Polish equivalents of Greek lexemes, such as didaskalos, epistates, including Hebrew loanwords in Greek, such as rabbi and rabbuni. They are used mainly as appellative forms, in a direct address to a person. Those words occur in both the main text as well as in glosses, especially in Protestant texts. Their number, greater than in Greek and Latin, indicates creative consideration of the performed translation and the process of improvement of the translation workshop and in case of heterodox translations — the need to update vocabulary associated with Catholicism, e.g. uczyciel by Szymon Budny. To a minor extent the lexis of this group confirms the denominational differences.